2011
DOI: 10.1088/2041-8205/745/1/l4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes of Photospheric Magnetic Field After Tether-Cutting Reconnection and Magnetic Implosion

Abstract: The rapid, irreversible change of the photospheric magnetic field has been recognized as an important element of the solar flare process. This Letter reports such a rapid change of magnetic fields during the 2011 February 13 M6.6 flare in NOAA AR 11158 that we found from the vector magnetograms of the Helioseismic and Magnetic Imager (HMI) with 12 minute cadence. High-resolution magnetograms of Hinode that are available at ∼−5.5, −1.5, 1.5, and 4 hr relative to the flare maximum are used to reconstruct a three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
76
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 50 publications
20
76
1
Order By: Relevance
“…The two main darkening/decaying areas, "E" and "D," indicated by the white/black arrows and enclosed by the white/black boxes, can be more obviously discerned in the difference intensity image (panel (c)), in which dark/bright features indicate enhancing/decaying areas in the post-flare image. In line with some previous observations (Wang & Liu 2010;Liu et al 2012;Petrie 2012), outstanding changes in the horizontal components of vector fields, B h , also took place in E and D. In order to exhibit these changes distinctly and concretely, in the vector magnetograms (panels (d1) and (d2)), the vertical components of vector fields, B r , are plotted as grayscale background superposed with isogauss contours, while the horizontal components are represented by the short arrows aligned to the field direction, with varying color proportional to the different field strengths as indicated by the color bar. For clarification, B h | | less than 400 G are not overplotted.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The two main darkening/decaying areas, "E" and "D," indicated by the white/black arrows and enclosed by the white/black boxes, can be more obviously discerned in the difference intensity image (panel (c)), in which dark/bright features indicate enhancing/decaying areas in the post-flare image. In line with some previous observations (Wang & Liu 2010;Liu et al 2012;Petrie 2012), outstanding changes in the horizontal components of vector fields, B h , also took place in E and D. In order to exhibit these changes distinctly and concretely, in the vector magnetograms (panels (d1) and (d2)), the vertical components of vector fields, B r , are plotted as grayscale background superposed with isogauss contours, while the horizontal components are represented by the short arrows aligned to the field direction, with varying color proportional to the different field strengths as indicated by the color bar. For clarification, B h | | less than 400 G are not overplotted.…”
Section: Resultssupporting
confidence: 92%
“…In more recent years, high-resolution white-light sunspot observations revealed some changes in photospheric fine structures caused by flares, e.g., disappearing penumbra fibrils and transition bright grains could evolve into faculae (Wang et al 2012a), granulation pattern could evolve to alternating dark and bright penumbra fibril structures (Wang et al 2013), and there were remarkable high-speed flows along the flaring PILs (Shimizu et al 2014). On the other hand, the photospheric vector magnetic-field observations showed that the horizontal magnetic fields increased rapidly and permanently around the central PILs (Wang & Liu 2010;Liu et al 2012;Petrie 2012;Sun et al 2012;Wang et al 2012bWang et al , 2012c, while they decreased significantly in the outer regions (Wang et al 2009;Li et al 2011;Sun et al 2012). These results thus suggested that, after major flares, the magnetic fields often became more horizontal in the central PIL regions but more vertical in the decaying penumbra regions.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the footpoints of the sigmoid arms show compact brightenings in 304 Å (denoted by the green arrows at 11:14:33 UT). This sequence of converging J-loops being proceeded by chromospheric footpoint brightenings is consistent with predictions for impulsive flaring at coronal temperatures (Imada et al 2015) and the process of tether-cutting reconnection (TCR; Moore et al 2001;Sterling & Moore 2003;Liu et al 2012). In the tether-cutting process, the reconnection is accompanied by high-temperature radiation.…”
Section: Resultssupporting
confidence: 88%
“…2 pixel −1 ; 10 s cadence) obtained by the BBSO 10 inch telescope. Right after the onset of )), which are interpreted as footpoints of quasi-separatrix layers during the reconnections in the vertical flare current sheet (e.g., Schrijver et al 2011;Liu et al 2012a). As the flare progressed, the double J-shaped ribbons expanded into a dumbbell-shaped brightening.…”
Section: Wave Onset and Propagationmentioning
confidence: 99%